Pengaruh Pemahaman Akuntansi, Pemanfaatan Sistem Informasi Akuntansi, dan Peran Internal Audit Terhadap Kualitas Laporan Keuangan : (Studi Kasus Pada PT. Kereta Api Indonesia (Persero) Kota Surabaya) - Stefani Sindita Sari; Gabrielle Michaela Krisvi; Irda Agustin Kustiwi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to assess the influence of accounting understanding, use of accounting information systems, and the role of internal audit on the quality of financial reporting at PT Kereta Api India (Persero) Surabaya City. The research method used is quantitative, and the research approach involves descriptive analysis using primary data. Analysis was carried out using SPSS to carry out Validity Tests and Reliability Tests. As an employee at PT Kereta Api Indonesia (Persero), you are part of the sample population of the general accounting and taxation department, which is also the accounting department, responsible for finance, budgeting and management. Accounting knowledge, use of accounting information systems and internal audit play an important role in controlling the quality of financial reports.